Pricing Strategy of Sudut Pajak Website Service at Politeknik Negeri Batam - Anggraini, Ria; Arniati, Arniati; Rahmawati, Diah Putri (Journal of Applied Business Administration, 2024)
This research aims to explore the pricing strategies for tax services offered on the Sudut Pajak website at Politeknik Negeri Batam. The study combines the aspects of the SBIFT model"”Scope, Base, Influence, Formula, and Temporal Right"”along with qualitative research methods and website content analysis to assess the way service providers organize their pricing. The results show that tax service providers largely employ packaged services as a means of luring customers, and that cost-based pricing functions as a fundamental instrument for making decisions. The report also notes the application of per-unit pricing based on service volume, open pricelists for efficient pricing communication, and subscription models for defining client usage windows and improving revenue stability. These insights contribute to the understanding of how tax service providers can implement effective pricing strategies to improve service delivery, foster customer loyalty, and ensure profitability. The study encourages further exploration of pricing models in the context of tax services to refine approaches and enhance service effectiveness.